Bimanual Pelvic Examination is Not Sensitive for Fibroid Diagnosis [30G]. (May 2018) - Ahmed, Farah; Green, Isabel; Stewart, Elizabeth A.; Laughlin-Tommaso, Shannon
Abstract : INTRODUCTION: Bimanual pelvic examination is often performed for symptoms related to uterine fibroids (UF). We evaluated the clinical utility of this exam at the time of UF diagnosis in a community setting. METHODS: Retrospective sample of women diagnosed with UF between 2006 and 2010 in the Rochester Epidemiology Project, a population-based records-linkage system. Cohort includes a sample of women who had a pelvic examination within 12 months of UF diagnosis (n=141). Abnormal pelvic exam was defined as abnormal uterine size or shape, or any adnexal mass or fullness recorded by healthcare provider. We examined clinical and imaging characteristics using chi-squared for categorical and t tests for continuous data. Data reported as percentage or mean ± standard deviation. Volumes of the uterus and largest fibroid were calculated using the prolate ellipsoid formula. RESULTS: Women with UF and a normal pelvic exam (n=73) were younger than women with abnormal exam (n=68) (44.7±7.1 vs 46.9±5.4 years, P=.05), and had a higher BMI (29.4 ± 6.5 vs 26.6 ± 5.0 kg/m 2, P=.007). Women with abnormal exam had significantly larger uterine volumes (226.0 ± 151.8 vs 150.9 ± 97.9 cm³, P=.005) and fibroid volumes (61.1±81.1 vs 19.9±52.8 cm³, P=.005). Abnormal examination was more frequently documented by gynecology providers (57.4%) than other providers (42.7%, P=.04). Fibroid symptoms were not associated with abnormal examination. CONCLUSION: Fifty-two percent of women with fibroids had a normal bimanual examination. Thus, a high suspicion of fibroids should prompt imaging. Lower BMI and larger uterine and fibroid dimensions increase fibroid diagnosis on pelvic examination.